Derangements in pulmonary function among informal fuel sellers exposed to vapors in Maicao, Colombia - Jaramillo Ordoñez, Juan Carlos (2023)
Objective: To determine the effects of fuel vapor exposure on pulmonary function among informal sellers. Methods: Cross-sectional study carried-out among informal fuel sellers in Maicao, Colombia. Sociodemographic data were gathered as well as pulmonary function by spirometry, pulse oximetry and evaluation of biomass exposure. Results: 74 patients were evaluated; 87.8% were males, 71.6% of them had between 18 to 40 years of age; 21.6% (n=16) reported pulmonary diseases; 59.4% had a predicted FEV1 <80%; 68.9% had a predicted FVC <80% and 32.4% had a predicted FEV1/FVC < 70%. Among those who had abnormal spirometry, (n=45) 62.2% reported to had worked ≥5 years. The most common reported symptoms were dysphonia (14.8%), conjunctivitis (14.8), epigastric pain (10.8) and headache (9.45%). No statistically significant differences were found between spirometry alterations and history of p pulmonary diseases, mean oxygen saturations and presence of a respiratory disease. Conclusions: This study demonstrates that a significant proportion of informal fuel sellers exposed to fuel vapors in the Colombian-Venezuelan border had derangement of the pulmonary function measured by spirometry and that some of them reported symptoms and respiratory disease. Young male adults of low socioeconomic and educational levels with prolonged exposure to fuel vapors are mostly affected.